Insulin resistance in prostate cancer patients and predisposing them to acute ischemic heart disease. Issue 7 (29th July 2019) - Ray, Udayan; Bank, Sarbashri; Jayawardana, Madawa W.; Bhowmik, Jahar; Redwig, Frank; Jana, Pradipta; Bhattacharya, Suman; Manna, Emili; Kumar De, Subrata; Maiti, Smarajit; Roberts-Thomson, Philip; Parameswaran, Venkat; et al.
Abstract : Lack of insulin or insulin resistance (IR) plays a central role in diabetes mellitus and makes diabetics prone to acute ischemic heart disease (AIHD). It has likewise been found that many cancer patients, including prostate cancer patients die of AIHD. Previously it has been delineated from our laboratory that dermcidin could induce anomalous platelet aggregation in AIHD and also impaired nitric oxide and insulin activity and furthermore dermcidin was also found in a few types of cancer patients. To determine the role of this protein in prostatic malignancy, a retrospective case–control study was conducted and blood was collected from prostate cancer patients and healthy normal volunteers. So, we measured the level of dermcidin protein and analyzed the IR by Homeostasis Model Assessment (HOMA) score calculation. Nitric oxide was measured by methemoglobin method. HDL, glycated hemoglobin (HbA1c), BMI, hs-cTroponin-T were measured for the validation of the patients' status in the presence of Dermcidin isoform-2 (DCN-2). Multiple logistic regression model adjusted for age and BMI identified that the HOMA score was significantly elevated in prostate cancer patients (OR = 7.19, P <0.001). Prostate cancer patients are associated with lower level of NO and higher level of both proteins dermcidin (OR = 1.12, P <0.001) and hs-TroponinT (OR = 1.76, P <0.001). From the results, it can be interpreted that IR plays a key role in the pathophysiology of prostate cancer where dermcidin was the cause of IR through NO inhibition leading to AIHD was also explained by high-sensitive fifth generation cTroponin-T (hs-cTroponinT) and HbA1c level which are associated with endothelial dysfunction.